Iris microhaemangioma: a management strategy - Dharmasena, Aruna (International Journal of Ophthalmology Press, 2013)
AIM: To analyse previous literature and to formulate a management strategy for iris microhaemangiomas (IMH). METHODS: A review of the literature in English language articles on IMH. RESULTS: Thirty five English language articles fulfilled the criteria for inclusion to the study and based on the contents on these articles a management strategy was formulated. Age at presentation ranged from 42 to 80 years with no sex or racial predisposition. Most patients with IMH have no systemic disease but a higher incidence had been reported in patients with diabetes mellitus, myotonic dystrophy, chronic obstructive pulmonary disease (COPD) and several other systemic and ophthalmic co-morbidities. Most patients remained asymptomatic until they experienced a sudden blurring of vision due to a hyphaema. Some patients only develop a self-limiting single episode of hyphaema and therefore the laser or surgical photocoagulation of iris should be reserved for the cases complicated with recurrent hyphaema. In some patients, several laser photocoagulation sessions may be needed and the recurrent iris vascular tufts may require more aggressive treatment. Iris fluorescein angiography (IFA) is useful in identifying the true extent of the disease and helps to improve the precision of the laser treatment. Surgical excision (iridectomy) should only be considered in patients who fail to respond to repeated laser treatment. In some cases IMHs has been initially misdiagnosed as amaurosis fugax, iritis and Posner-Schlossman syndrome. CONCLUSION: Owing to its scarcity, there is no good quality scientific evidence to support the management of IMH. The authors discuss the various treatment options and present a management strategy based on the previous literature for the management for this rare condition and its complications.